Challenges and possible improvements for healthcare teams at outreach clinics in Nepal – a qualitative study - Ingrid Eriksen; Eirin Helene Rasmussen; Biraj Karmacharya; Seema Das; Elisabeth Darj; Maria Lisa Odland (Global Health Action)
Background All Nepalese citizens have the right to high-quality healthcare services free of charge. To achieve this, healthcare services for the rural population in Nepal need to be improved in terms of personnel, medicines, and medical equipment. Objectives To explore challenges and possible improvements healthcare personnel experience when travelling to rural parts of Nepal to provide healthcare. Method Data was collected from various health professionals using focus group discussions at Dhulikhel Hospital in Nepal. The data were transcribed and analysed using Systematic text condensation. Results Twenty-two professional healthcare personnel participated in five group discussions. Four categories emerged from the collected material: Finding ORC services being underutilised, Wanting to fulfil tasks and do a good job, Facing inadequate resources, and Seeing the need for improved organisation and cooperation. There was consensus that rural clinics are important to maintaining health for the rural population of Nepal. However, there was frustration that the rural population was not benefitting from all available healthcare services due to underutilisation. Conclusion Rural healthcare clinics are not utilised appropriately, according to healthcare workers at the rural outreach clinics. Potential ways of overcoming the perceived challenges of underutilising available healthcare services include financial and human resources. The rural population´s health awareness needs to be increased, and the work environment for rural healthcare workers needs to be improved. These issues need to be prioritised by the government and policymakers.